Implementasi BUMDes (Badan Usaha Milik Desa) Ngudi Berkah dalam Meningkatkan Pendapatan Asli Desa Kedu - Minarti, Ayuk; Sariyekti, Eko; Wahyuningsih, Effi (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
State-owned enterprise or Badan Usaha Milik Desa (BUMDes) is one of the government’s program in support state to be independence. The program is an opportunity for states in Indonesia. Several BUMDes have billions of rupiah in turnover and make a large contribution to local owned-source revenue, so that state independence can be achieved. On the other hand, poor manajement result in BUMDes make BUMDes not develop, stagnant and remains only in name. One of the BUMDes that s currently active is BUMDes Ngudi Berkah Kedu. Which was established in 2019 and started operating in 2020. Furthermore in 2021 received status as Growing BUMDes. This study aims to determine the implementation of the BUMDes Ngudi Berkah Kedu and its contribution in increasing the local owned-source revenue. This is a qualitative descriptive study using a qualitative approach. The data used are primary and secondary data obtained through observation, interviews and documentation. Data analysis was carried out using the Miles and Huberman (1984) model including data collection, data reduction, data presentation, and conclusions drawing/ verification. The findings show that the implementation of the BUMDes Ngudi Berkah has been carried out based on the established legal basis. Its establishment and management uses the principles of openness and responsibility, participatory, prioritizing local resources, sustainable, cooperative and emancipatory. The principle of professionalism has not been implemented optimally. With regard to its contribution to increasing the local owned-source revenue, the BUMDes Ngudi Berkah has been able to contribute to an increase in the local owned-source revenue, the amount of contribution given is around 3% -7% of the total receipt of Kedu village's original income.